Investment and abandonment behavior of rural households: An empirical investigation - Hill, Ruth Vargas (Wiley, 2010)
This article uses models of irreversible investment under uncertainty to examine the investment and abandonment behavior of poor rural households. It considers the decision of Ugandan coffee‐farming households to invest in or abandon coffee trees. The observed levels of investment and abandonment are found to be consistent with models of investment that allow for irreversibility, uncertainty, fixed costs, and liquidity constraints. The findings highlight the importance of addressing volatility, irreversibility, fixed costs, and liquidity constraints in order to increase households’ responsiveness to changes in the fundamentals and to enable households to recover from shocks to their capital stock.